Chemical reaction rate determination I. numerical differential methods - Jesudason, C.G. (2010)
Chemical reaction rates are determined mainly by linear plots of reagent concentration terms or its logarithm (depending on the order) against time with initial concentration -equivalent to the final property reading at infinite time- specified, which can be experimentally challenging. By definition, the rate constant is an invariant quantity and the kinetic equations follow this assumption. Different schemes have been used to circumvent specifying initial concentrations. In this sequel, the differential method using nonlinear analysis (NLA)focuses on the gradient which provides a sensitive measure of the rate constant that does not require specification of initial concentrations and the results are compared with those derived from standard methodologies from an actual chemical reaction and one simulated ideally. It is shown that the method is feasible. A novel integral approach based on a principle of induced parameter dependence (PIPD) is introduced in the second sequel. It is concluded that elementary nonlinear methods in conjunction with experiments could play a crucial role in providing accurate values of various parameters of interest.